Penyelesaian Kredit Bermasalah pada Pinjaman Kredit Usaha Rakyat di Bank BRI Cabang Karanganyar Unit Tasikmadu - Putri Aji Hapsari; Ashinta Sekar Bidari (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
People's Business Credit (KUR) is a financing program distributed by the government through banking institutions, including Bank Rakyat Indonesia (BRI), to support Micro, Small, and Medium Enterprises (MSMEs) and cooperatives. In its implementation, KUR credit is not free from various problems, one of which is non-performing loans. This study aims to determine the factors causing non-performing loans and efforts to resolve them in KUR loans at Bank BRI Karanganyar Branch, Tasikmadu Unit. The method used in this study is qualitative research, with data sources derived from primary, secondary, and tertiary legal materials. Data collection techniques were conducted through direct interviews with relevant parties. The results show that the main causes of non-performing loans are divided into two major factors. First, external factors, namely those originating from the customer. This problem is generally related to the customer's inability to pay installments due to business failure. Second, internal factors, such as the failure of creditworthiness analysis by bank officers, resulting in prospective debtors who are actually unworthy actually receiving loans. In resolving non-performing loans, BRI Bank's Karanganyar Branch, Tasikmadu Unit, applies five main methods: (1) changing the loan interest rate, (2) reducing fines or penalties, (3) reducing the outstanding principal, (4) extending the loan term, and (5) selling collateral. Additionally, there are also settlement methods that involve a combination of these five methods, depending on the debtor's circumstances and the agreement between the two parties.